Christians’ social perception of climate change and poverty: A study of the Nkroanza south district assembly - E. Owusu; V.S. Gedzi; E. Obimpeh-Quayson (Acta Theologica)
Climate change and its associated risks continue to dominate global discourse, considering the negative effect on human existence. Despite a plethora of scientific publications on climate change with its associated risks globally and locally, there is limited empirical evidence from the Ghanaian Christian context. Consequently, hardly any research has been done to examine the social perception of Christians on climate change. A quantitative study was conducted using self-prepared questionnaires to examine the knowledge and social perception of Christians on climate change in the Nkroanza South Municipal. It was established that respondents understand climate change from the context of their indigenous knowledge systems. The study chi-square test (25.167, df) = 10, p = 0.005, indicated a statistically significant association between the duration of residence in the community and climate change awareness. The study further found a divergence in the general perception of climate change among the Christian community.